(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
Rarely, neuroendocrine cells, the pancreas, and the gastrointestinal system are the sites of origin for neuroendocrine carcinoma (NEC). Even though it looks like an adenocarcinoma, well-differentiated NEC exhibits more benign biological behavior [1]. Undifferentiated NECs, however, may have invasive and metastatic features, according to one report [2]. Compared to NEC, primary hepatic neuroendocrine tumors (PHNET) are less common, grow more slowly, and have the potential to progress into malignancy. Carcinoid syndrome affects a very small percentage of people. PHNETs and hepatocellular carcinoma (HCC) share similarities on CT and MRI scans; however, patients with PHNETs tend to have a better prognosis. Because CT and MRI scans are sensitive in identifying primary liver lesions and metastases, these methods may assist medical professionals in determining the best course of treatment and increase patient survival.